Plantation distance, frequency and cutting height on the biomass production of Tithonia diversifolia collection 10 during the year - Ru?z, Tom?s E.; Febles, Gustavo; D?az, Humberto (Cuban Journal of Agricultural Science, 2012)
Two experiments were conducted, for two years each, to study the effect of combining plantation distance, frequency and cutting height on the annual biomass production of Tithonia diversifolia collection 10. A random block design in factorial arrangement with four repetitions was applied in each experiment to analyze the following factors: plantation distance (0.5 and 1.0 m) and cutting height (5, 10 and 15 cm) (experiment 1 A); cutting frequency (40, 60 and 80 d) and cutting height (5, 10 and 15 cm) (experiment 2 A). There was interaction for the factors under study. During the rainy season, there was higher yield (P < 0.001) in the experiment 1 with the lowest plantation distance (5.0 ? 5.5 t/ha DM) and there was no effects in respect to the cutting height. The lowest plantation distance in the dry season had better performance in respect to yield (3.5-4.5 t/ha DM) and there was effect of the cutting height with lower yield (3.5 t/ha DM) at 5 cm (P< 0.01). In the experiment 2, the best performance (P< 0.001) was at 10-15 cm height and frequency of 80 d during the dry season (0.85-0.90 t/ha DM). The cutting height of 15 cm had (P< 0.001) the best yields together with the frequency of 60 d for the rainy season (1.7 t/ha DM). Higher yield was reached at distances of 0.50 m between furrows for both seasons. The plantation should be cut at heights between 10 and 15 cm, with cutting frequency of 60 and 80 d in the rainy and dry season, respectively. Key words: plantation distance, cutting frequency, cutting height, biomass production.